PENINGKATAN KETERAMPILAN BERBAHASA INGGRIS BAGI KARANGTARUNA DAN IBU-IBU PKK DESA SUNTEN JAYA - Satria Raditiyanto; Heni Haryani; Mutiara Indah Nirmala Dewi; Thomson Radesman Lingga; Sri Handayani; Nanan Kandagasari; Encep Rustandi; Suharyanto Suharyanto; Cevi Mochamad Taufik (Jurnal Abdimas Sang Buana, 2023)
English is still considered a third language after the unified language of Indonesia and mother tongue. In the current conditions, when various regions around the world are connected to a global network, English is absolutely mastered. English is the main language that can connect all citizens of the world. As a language of instruction that facilitates the exchange of various potentials owned by a village, opens opportunities to foster interest in visiting world citizens, or opens up investment possibilities, or transactions to purchase regional wealth resources. Therefore, through community service activities, the English Literature lecturer at the National University of the Republic of Indonesia aims to provide English language skills to youth who are members of Youth Organizations and mothers who are members of the Family Welfare Development (PKK) in Sunten Jaya Lembang village, West Bandung Regency. PkM activities are carried out using lecture and discussion methods to provide proper understanding and teaching regarding English symbols that must be understood. The results obtained from this activity are awareness of the need to have English language skills, in order to be able to promote Sunten Jaya as an agricultural area worthy of being used as a tourist destination.Keywords: English, promotion, tourism, potential, Sunten Jaya